A Rawlsian dual duty of assistance - Seleme, Hugo Omar (2010)
This paper seeks to specify the requirements that follow from the Rawlsian duty of assistance.  In order to determine them, the hypothesis I will defend is that this duty is a specification of the natural duty of justice. This interpretation has several advantages: a) It facilitates the task of appreciating how one of the most important parts of the Rawlsian conception of international justice presented in The Law of Peoples is connected with the natural duty of justice presented in A Theory of Justice. b) It enables one to appreciate a new requirement of the duty of justice overlooked by Rawls:  the duty of contributing to maintaining well-ordered foreign institutions. c) This new requirement enables one to appreciate the critical potential of justice as fairness in relation to one of the most pressing problems nowadays: the foreign debt of developing countries.